Acoustical Properties of 3-α-Furyl Acrylic acid in Protic and Aprotic Solvents - Baluja, Shipra; Parsania, P.H. (Asian Journal of Chemistry, 2010)
Ultrasonic sound velocities of 3-α-furyl acrylic acid (FAA) solutions in different solvents such as dioxane, ethanol, acetone, benzene and toluene were measured at 30ºC using single crystal interfermeter operating at frequency of 1 MHz using sound velocity (U), density (ρ) and viscosity (η) data of FAA solutions in above mentioned solvents. Various acoustical parameters such as adiabatic compressibility(βad), specific impedance (Z), apparent molar compressibility (φk), relative association (RA), solvation number (Sn), intermolecular freepath (Lf), internal pressure (π), Rao's molar sound function (R), molar compressibility (W), the vander Waals constant (b) and the relaxation strength (r) have been calculated. Bachem's and Gucker's laws have been found to be applicable.